Migratory raptors in Imam Turki Bin Abdullah royal nature reserve: a biodiversity hotspot in Saudi Arabia - Bilal Kabeer; Yehya K. Shahadah; Rayan M. Raseni (Пернатые хищники и их охрана)
Saudi Arabia, encompassing 1,969,000 km2 , is a home to rich array of bird species across its diverse ecosystems. The Imam Turki bin Abdullah Royal Reserve (ITBA) reserve, situated in the northern part of the kingdom, holds a varied topography and habitat diversity that make it a haven for migratory birds.